Information Now: A Graphic Guide to Student Research - Matt Upson, , C. Michael Hall, (University of Chicago Press, 2015)
Every day researchers face an onslaught of irrelevant, inaccurate, and sometimes insidious information. While new technologies provide powerful tools for accessing knowledge, not all information is created equal. Valuable information may be tucked away on a shelf, buried on the hundredth page of search results, or hidden behind digital barriers. With so many obstacles to effective research, it is vital that higher education students master the art of inquiry.